Linux Malware Incident Response : an Excerpt from Malware Forensic Field Guide for Linux Systems. - Malin, Cameron H. (Elsevier Science, 2013)
The Syngress Digital Forensics Field Guides series includes companions for any digital and computer forensic investigator and analyst. Each book is a "toolkit" with checklists for specific tasks, case studies of difficult situations, and expert analyst tips. This compendium of tools for computer forensics analysts and investigators is presented in a succinct outline format with cross-references to supplemental appendices. It is designed to provide the digital investigator clear and concise guidance in an easily accessible format for responding to an incident or conducting analysis in a la.